Hypertriglyceridemia in Infants and Children with Hypernatremia - Ahmed, Fathelrahman E; Lutfi, Mohammed F (International Journal of Health Sciences, 2015)
Background: Hypertriglyceridemia in association with hypernatremia was reported in a few children; however, studies exploring this association are limited. Objective: To determine the pattern of change in serum triglycerides levels in hypernatremia patients. Design and setting: A prospective case-control study done at North West Armed Forces Hospital, Tabuk, Saudi Arabia from April 2008 to March 2011 Patients and method: A serum triglycerides and sodium were measured in 16 patients with hypernatremic dehydration as a study group and 14 patients with isonatremic dehydration as a control group. The trend of serum sodium and triglycerides was followed during treatment in the study group. Results: There were 6 boys and 8 girls in the control group (isonatremic dehydration). Their age ranged between 4 months and five years (M±SD = 1.7±1.3 years). In the study group (hypernatremic dehydration), there were 6 boys and 10 girls. The age range was 2-14 months (M±SD = 0.6±0.4 years). The serum sodium and triglycerides (M±SD = 165.8±9.1 mmol/l, 5.1±8.1 mmol/l respectively) were significantly higher compared with the control group (M±SD = 137.5±3.9 mmol/l, 0.7±0.3 mmol/l and P < 0.001, P < 0.05 respectively). Duration of symptoms in patients with hypernatremic dehydration (M±SD = 2.9±2.4 days) were comparable to control group (M±SD = 2.0±0.9 days, P = 0.18). Four patients from the study group had normal serum triglycerides (M±SD = 1.1±0.1 mmol/l). With treatment, serum sodium was normalized in all patients followed by serum triglycerides. Conclusion: Hypertriglyceridemia is present in most children with hypernatremia and it disappears when serum sodium returns to normal. Keywords: Dehydration, Hypernatremia, Hypertriglyceridemia.